2020
DOI: 10.4193/rhin19.184
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of different endoscopic sinus surgery in recurrent chronic rhinosinusitis with nasal polyps and asthma

Abstract: Background: Patients with chronic rhinosinusitis with nasal polyps (CRSwNP) and asthma have poorer outcomes after functional endoscopic sinus surgery (FESS) and higher recurrence rate. The aim of present study was to investigate the long-term clinical outcomes of extended surgical strategies for patients with recurrent CRSwNP and asthma.Methods: Eighty-one patients with CRSwNP and asthma were enrolled in this 5-year prospective study. They were randomly assigned to undergo FESS, radical endoscopic sinus surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 41 publications
5
80
2
2
Order By: Relevance
“…In the presence of co‐morbid conditions such as asthma and nasal polyposis, the extent of surgery may influence rates of polyp recurrence. In patients with asthma and nasal polyposis, Zhang et al found that the addition of a Draf III frontal sinusotomy improved polyp recurrence rates in the first year after surgery compared to standard ESS (59% vs 89%); however, by year 3 there were no differences in polyp recurrence rate, with a 96% rate of polyp recurrence in both groups 2020 …”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…In the presence of co‐morbid conditions such as asthma and nasal polyposis, the extent of surgery may influence rates of polyp recurrence. In patients with asthma and nasal polyposis, Zhang et al found that the addition of a Draf III frontal sinusotomy improved polyp recurrence rates in the first year after surgery compared to standard ESS (59% vs 89%); however, by year 3 there were no differences in polyp recurrence rate, with a 96% rate of polyp recurrence in both groups 2020 …”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…Further investigations have revealed that a Th2-biased inflammation pattern underlying the eosinophilic infiltration is predominant among the Caucasian CRSwNP population in Western countries, whereas over 50% of CRSwNP patients in the Eastern countries present a Th1/Th17-skewed inflammation involving non-eosinophilic accumulation [20, 49-53]. CRSwNP still has a high propensity for recurrence regardless of significant improvement being facilitated by ESS intervention [13, 54-56]. Previous studies have reported that better surgical interventions or the long-term application of postoperative intranasal GCs may prevent or delay recurrence [7, 9, 13, 57].…”
Section: Discussionmentioning
confidence: 99%
“…CRSwNP still has a high propensity for recurrence regardless of significant improvement being facilitated by ESS intervention [13, 54-56]. Previous studies have reported that better surgical interventions or the long-term application of postoperative intranasal GCs may prevent or delay recurrence [7, 9, 13, 57]. To date, novel parameters and biomarkers, in addition to tissue and peripheral blood eosinophil counts and percentages, have been proposed as predictive factors for recurrence and are worth further investigating, including CLC [33, 34, 41, 58-61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations